Edukasi Smart Citizens Melawan Hoaks: Mengenal Zat Kimia Aman Dan Berbahaya Dalam Makanan Melalui Aplikasi “Chemical Quest” Di SMA Negeri 1 Percut Sei Tuan - Abdinur Batubara; Ramsul Nababan; Nurhalimah Br Ginting; Hary Fitra Ramadani (CV. Multi Kreasi Media, 2024)
Hoaxes about chemicals in food have spread in society and have caused misinformation that has a negative impact on food safety. Many natural and added chemicals in food are considered dangerous without strong scientific evidence. This community service aims to educate students at SMA Negeri 1 Percut Sei Tuan about the safety and dangers of chemicals in food using the educational application